2021
DOI: 10.3389/fcimb.2021.741147
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Primer Design Minimizes the Risk of PCR Failure Caused by SARS-CoV-2 Mutations

Abstract: The coronavirus disease 2019 (COVID-19) has caused and is still causing tremendous damage to the global economy and human health. Qualitative reverse transcription-PCR (RT-qPCR) is the golden standard for COVID-19 test. However, the SARS-CoV-2 variants may not only make vaccine less effective but also evade RT-qPCR test. Here we suggest an innovative primer design strategy for the RT-qPCR test of SARS-CoV-2. The principle is that the primers should be designed based on both the nucleic acid sequence and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…When the number of available SARS-CoV-2 genomes was limited, choosing conserved target genes was a crucial factor for the design of optimal PCR primers (Li et al 2020 ), and optimization of laboratory test protocols was important for effective detection (Won et al 2020 ). Checking for abundant splicing variants (Park et al 2020 ) and designing primers that can anneal to non-degenerate codons (encoding tryptophan) at the 3’-ends of sequences (Dong et al 2021 ) were also suggested to ensure highly sensitive viral nucleic acid detection. On the contrary, our current study does not rely on previous knowledge of the structural aspects of conserved genes, and our approach can be scaled easily as the number of SARS-CoV-2 genomes increases.…”
Section: Discussionmentioning
confidence: 99%
“…When the number of available SARS-CoV-2 genomes was limited, choosing conserved target genes was a crucial factor for the design of optimal PCR primers (Li et al 2020 ), and optimization of laboratory test protocols was important for effective detection (Won et al 2020 ). Checking for abundant splicing variants (Park et al 2020 ) and designing primers that can anneal to non-degenerate codons (encoding tryptophan) at the 3’-ends of sequences (Dong et al 2021 ) were also suggested to ensure highly sensitive viral nucleic acid detection. On the contrary, our current study does not rely on previous knowledge of the structural aspects of conserved genes, and our approach can be scaled easily as the number of SARS-CoV-2 genomes increases.…”
Section: Discussionmentioning
confidence: 99%
“…Using this principle, they designed primer pairs that targeted the nucleocapsid (N) gene. Their design rendered similar sensitivity and specificity to the US and Chinese CDC-validated primers, but more importantly, performance was not influenced by frequently occurring mutations ( Dong et al, 2021 ).…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Both methionine and isoleucine are nonpolar amino acids. Previous reports have suggested that M322I could bring about a slight decrease in N protein thermal stability (15) and might affect the host immune response to COVID-19 viral infection (16).…”
Section: Signature Mutations Of the Ba237 Lineagementioning
confidence: 99%